If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = lx + -2l Reorder the terms: Y = -2l + lx Solving Y = -2l + lx Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -2l + lx
| r^2+7r-60=0 | | 10=x(25) | | x^2+196=y^2 | | 0.11x+0.04(7000-x)=630 | | -7-7/20-13 | | k^2+6k-40=0 | | 54x^2-256x=11x-325 | | 5x+6=-21 | | 6x-12+8x=5 | | 17q+5=12q^2 | | 1.3+0.3x=0.7x-4.3 | | 3A+C-A+4C= | | 2(2u-9)=50 | | f(x)=x^2+3x-9 | | 6x^2-12+8x=5 | | c-0.15c=119 | | 2ln(3x)+6=24 | | 3(g-2)=7g-18 | | (x^2+x-42)= | | 5a^2-9a-8=0 | | 2.5(n-6.1)=11.4 | | p+0.07p=203.3 | | y=-x^2+3x-9 | | 72-3x=100-5y | | si(4x)=-2sin(2x) | | 8m+12=12m | | 12x+73=10x-60 | | 0.25p-1.5=3.5 | | 0.46x+24.90= | | 7(9x-7)=4 | | 5+Y+5=20-5 | | .016y-.08=.04+.06y |